Learning Media and Participant Engagement in an English Training Class at Balai Pelatihan Vokasi dan Produktivitas Bantaeng - Rostina Rostina (CV Projurnal Mitra Publikasi, 2025)
Learning media are crucial in English language teaching, particularly in vocational training contexts where learners have specific practical and occupational needs. This study aims to examine the types of learning media used and participant engagement during English learning activities in a vocational training institution. A qualitative case study design was employed in an English training class at Balai Pelatihan Vokasi dan Produktivitas (BPVP) Bantaeng. The study was based on reflective teaching practices, classroom observations, and document analysis conducted over a four-year period from 2019 to 2022.The findings show that various types of learning media were used in the training class, including digital media, audio-visual media, and printed instructional materials. These media were supported by adequate classroom facilities and infrastructure. Participant engagement was observed in behavioural, emotional, and cognitive dimensions, particularly during interactive, media-supported, and vocationally relevant activities. Digital and audio-visual media, such as videos and interactive tasks were found to encourage active participation and positive learning attitudes. However, the study also identified several challenges in the use of learning media, including technical constraints, time limitations, differences in participants’ digital readiness, and instructor preparedness. These challenges affected the consistency and depth of media use during learning activities. Overall, the study suggests that learning media can effectively support participant engagement in vocational English training when they are carefully selected, contextually relevant, and supported by appropriate instructional strategies. This research contributes context-specific insights into learning media use and engagement in vocational EFL settings.